ON THE BIOLOGY OF THE PENAEID PARAPENAEOPSIS SCULPTILIS (HELLER) IN THE BOMBAY AREA - Sukumaran, K K; Rajan, K N (Indian Journal of Fisheries, 2011)
Male and female Paiapenaeopsis sculptilis in the fishery registered monthlyaverage growths of 5.88 mm and 8.17 mm, respectively. The young prawns recordedfaster rate of growth, about 15 mm per month. In the inshore fishery thesmallest female with fully matured ovary measured 88 mm in length, whereas inthe Arnala creek the prawns measuring 71 mm and above were found to be mature.Spawning is year-round with two peaks, one during February-March andanother during July-November. The chi-square values at 5% probability levelshowed that the observed proportion of males in difi'erent months of the yearsexcept 1969 were statistically significant. Sizewise distribution of sex ratio revealedthat males were predominant in the sizes within 78-98 mm and females outnumberedmales in the rest of the sizes.